Chitosan nanoparticles loaded with minocycline targeting osteomyelitis - Zegre, Miguel (2022)
Effective control of osteomyelitis (bone infection) with reduced toxicity is a current challenge. Targeted and controlled drug delivery systems allow: decreased toxicity, upgraded drug targeting, and improved therapeutic effect. Strategy: a) Innovative chitosan nanoparticulate system: nanoparticles loaded with minocycline (antibacterial), and alternative as a local delivery system; b) Nanoparticles and biofilms: advantages: enhanced bioavailability, targeted delivery of antibiotics magnification, local release of antibiotics, controlled and sustained release, and protection against deactivating enzymes.